2012
DOI: 10.3136/fstr.18.235
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Ethanol from Saccharified Crops Mixed with Cheese Whey by the Flex Yeast Kluyveromyces marxianus KD-15

Abstract: Ethanol production from a mixture of wheat flour or potato tubers and cheese whey was examined using the flex yeast Kluyveromyces marxianus KD-15, a 2-deoxyglucose-resistant mutant of strain NBRC 1963 that can produce ethanol from sugar beet thick juice diluted with whey. Strain KD-15 simultaneously converted glucose and lactose to ethanol within 48 h, in media containing 10.0% to 15.0% (w/v) total sugars from saccharified filtrate and whey. For efficient production of ethanol from 15.0% (w/v) total sugars, KD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Integration of cheese whey into lignocellulose-to-ethanol processes in a multi-wastes valorization approach could allow the improvement and intensification of fermentation conditions to attain high ethanol concentrations by increasing the carbon source content in the substrate. Recently, this strategy of whey incorporation has been proposed for raw materials from first generation bioethanol such as: wheat flour (Jin et al, 2016), potato tubers and starch (Nakamura et al, 2012). Research works using this approach with lignocellulosic raw materials as substrate are still limited (Oke et al, 2016) and reported final ethanol concentration below 50 g/L (Fischer et al, 2013;Coman et al, 2015;Ferreira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Integration of cheese whey into lignocellulose-to-ethanol processes in a multi-wastes valorization approach could allow the improvement and intensification of fermentation conditions to attain high ethanol concentrations by increasing the carbon source content in the substrate. Recently, this strategy of whey incorporation has been proposed for raw materials from first generation bioethanol such as: wheat flour (Jin et al, 2016), potato tubers and starch (Nakamura et al, 2012). Research works using this approach with lignocellulosic raw materials as substrate are still limited (Oke et al, 2016) and reported final ethanol concentration below 50 g/L (Fischer et al, 2013;Coman et al, 2015;Ferreira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%